(3GdeSJaGO ef eHgeGJ GdeJf hGdGSfGOs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CaVd Hg hHYO aEf ef GdeYdhe GdhGVM Gf CLd GdYdhe HYO cJGH Gddg GdefRd , Yde SfI fHjg GdeQSd s
(3BNQgG (B:s
(3PcQg ehGdOjge hhaGJge JQcJ PcQ Pdc EP djS ef GdeHgeGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3cJH eShOJg YHO GdQMef Hf MSf GdebGHQUi SfI (B906 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: (3GdGQHYGA YTQ LeGOi GdGNQI (B788(3g`s
(3GdfSNI HgG EWGQGJ s
Keywords: (3eJaQbGJs